Pengaruh Media Pembelajaran Pop Up Book Berbasis Cerita terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun di TK Negeri Pertiwi Pullauweng Bantaeng - Husnun, Nurul; Bachtiar, Muhammad Yusri; Amriani, Sri Rika (Innovative: Journal Of Social Science Research, 2024)
This research is a quasi-experimental research which aims to determine the effect of story-based pop up book learning media on the speaking abilities of children aged 5-6 years at Pertiwi Pullauweng Bantaeng State Kindergarten before and after being given treatment and to find out whether or not there is an effect of pop up book learning media. on the speaking ability of children aged 5-6 years at Pertiwi State Kindergarten Pullauweng Bantaeng. The independent variable in this research is pop up book learning media and the dependent variable in this research is speaking ability. The population in this study were 30 students at Pertiwi State Kindergarten Pullauweng Bantaeng. Sampling in this research used purposive sampling. The sample in this study consisted of 28 children, divided into 14 children as the experimental group and 14 children as the control group. The data analysis techniques used are descriptive statistical analysis and non-parametric analysis. The results of the data analysis obtained were Asym (2-tailed) = 0.01<0.05. H1 was accepted and H0 was rejected, meaning that speaking ability in the experimental class was better than in the control class, this proves that pop up book learning media has a significant influence on ability. talking to young children.